2016
DOI: 10.1111/psj.12164
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Organizational Failure in the Milwaukee School Voucher Program

Abstract: In this article, we utilize 25 years of data on the Milwaukee voucher program to test the relationships among organizational liabilities of newness, institutional affiliation, market‐share, and regulatory environment on the cumulative risk of school failure. Overall, we find that 41 percent of all private voucher schools operating in Milwaukee between 1991 and 2015 failed. Start‐up voucher schools, and those unaffiliated with a larger institution, have comparatively higher failure risk over time. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…The fourth theory refers to the issue of public legitimacy. Ford and Andersson (2016) utilize this approach in their study of the lifecycle of private voucher schools in Milwaukee, speculating that the quick failure rate of many entrepreneurial private schools is a result of their failure to gain legitimacy in the eyes of parents. Studies premised on questions of public legitimacy rely on external stakeholder perceptions of a public or nonprofit organization.…”
Section: What Is Population Ecology?mentioning
confidence: 99%
See 3 more Smart Citations
“…The fourth theory refers to the issue of public legitimacy. Ford and Andersson (2016) utilize this approach in their study of the lifecycle of private voucher schools in Milwaukee, speculating that the quick failure rate of many entrepreneurial private schools is a result of their failure to gain legitimacy in the eyes of parents. Studies premised on questions of public legitimacy rely on external stakeholder perceptions of a public or nonprofit organization.…”
Section: What Is Population Ecology?mentioning
confidence: 99%
“…Inertia could arguably be an asset or a liability in terms of organizational survival, depending on factors existing in the larger population of organizations. Consider the Milwaukee school voucher example used by Ford and Andersson (2016), who found that wellestablished private schools had higher survival rates than new entries into the voucher school marketplace. In that case inertia was an asset, and older schools were household names with a parent-accepted and established approach to educating students.…”
Section: What Is Population Ecology?mentioning
confidence: 99%
See 2 more Smart Citations
“…This inaugural issue’s final two articles address topics of educational policy, one focusing on multiple factors affecting school success, and the other on one specific element that may affect success at the individual student‐level. Building upon the previous work of Percy and Maier (), Ford and Andersson () explore the role of policy innovation through means of public entrepreneurship, specifically focusing on the failure rates of schools within the Milwaukee School Voucher Program. Using 25 years’ worth of data from 1991 to 2015, Ford and Andersson () find that start‐up voucher schools have substantial difficulty overcoming their “liability of newness” (Stinchcombe, ), leading the authors to conclude that school failure rate can be attributed to risks associated with high levels of entrepreneurial activity.…”
mentioning
confidence: 99%